Effect of whey protein purity and glycerol content upon physical properties of edible films manufactured therefrom - Ramos, Óscar L. (2013)
This manuscript describes the detailed characterization of edible films made from two different protein products e whey protein isolate (WPI) and whey protein concentrate (WPC), added with three levels of glycerol (Gly) e i.e. 40, 50 and 60%(w/w). The molecular structure, as well as barrier, tensile, thermal, surface and optical properties of said films were determined, in attempts to provide a better understanding of the effects of proteinaceous purity and Gly content of the feedstock. WPI films exhibited statistically lower (p < 0.05) moisture content (MC), film solubility (S), water activity, water vapor permeability (WVP), oxygen and carbon dioxide permeabilities (O2P and CO2P, respectively) and color change values, as well as statistically higher (p < 0.05) density, surface hydrophobicity, mechanical resistance, elasticity, extensibility and transparency values than their WPC counterparts, for the same content of Gly. These results are consistent with data from thermal and FTIR analyses. Furthermore, a significant increase (p < 0.05) was observed in MC, S, WVP, O2P, CO2P, weight loss and extensibility of both protein films when the Gly content increased; whereas a significant decrease (p < 0.05) was observed in thermal features, as well as in mechanical resistance and elasticity e thus leading to weaker films. Therefore, fundamental elucidation was provided on the features of WPI and WPC germane to food packaging e along with suggestions to improve the most critical ones, i.e. extensibility and WVP.